Beyond Meroni. What does it take to achieve a single market for network industries?. Issue 1 (2nd January 2022) - Pelkmans, Jacques; Simoncini, Marta
ABSTRACT: The EU single market for network industries has not been accomplished after more than three decades. The clearest shortcoming of this incipient EU internal market is the lack of EU independent regulators. This design failure reflects the uneasy equilibrium between the political (un)willingness of the Member States and EU institutions, legal constraints emerging from EU case-law and economic concerns. After providing economic evidence of a failing single market in network industries and of the awareness of this failure in EU institutions, we discuss the problematic EU governance in these sectors, followed by the Meroni doctrine (hindering the single market) and its recent revision by the Court of Justice. The adaptation of NRAs in EU-wide networks together with the emergence of weak EU agencies has helped to make NRAs more EU-oriented, but this is insufficient to arrive at a single market for network industries.